Cross well radar and vertical radar profiling methods for time lapse monitoring of rainfall infiltration - Strobach, Elmar; Harris, Brett; Dupuis, Christian; Kepic, Anton; Martin, M. (CSIRO, 2012)
The relationship between electromagnetic velocities derived from in-hole radar surveying and soil saturation can be exploited to map changes in recharge from rainfall infiltration in the vadose zone against time. We have completed time-lapse cross-well radar and vertical radar Profiling (VRP) experiments with the objective of monitoring rainfall infiltration during the winter season at two sites on the Gnangara Mound in the Perth Basin, Western Australia. Depth-velocity profiles have been derived from the direct transmission measurements. Results obtained from Vertical Radar Profiling and Zero vertical offset cross well profiling are evaluated and the influence of different geometries and test-site conditions are discussed. We find that zero vertical offset cross well radar experiments were highly repeatable. Further changes in ground conditions such as an increase in moisture content can be observed with great confidence. The interpretation of vertical radar profiles was more challenging. However both techniques successfully reveal the time-lapse response of water migrating through the unsaturated soil profile for the two trial sites.